Emaranhamento em sistemas de partículas indistinguíveis - Fernando Iemini de Rezende Aguiar (2011)
In this work we studied the issue of quantification of entanglement in quantum systems performing a detailed analysis since its fundamental principles, i.e, the postulates of the theory of entanglement measures, and thus justifying the expected properties of "good quantifiers" of entanglement. We presented some examples of entanglement measures for distinguishable particles, and we approach finally the case where the particles are indistinguishable from each other. We saw that, in this case, the quantification of entanglement is a subject of great controversies with different proposals to their approach, each with its own singular interpretation. After discussing these approaches, analysing their main characteristics and foundations, we present our proposed method to quantify them based on the use of entanglement witnesses.